READING AND WRITING PROGRAM IN THE CONTEXT OF A MUNICIPAL SCHOOL - Brandao, Carlos da Fonseca [UNESP]; Oliveira Trevelin, Fatima Gil de [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
The educational reforms of the 1990s regulated parameters and general guidelines through the National Education Guidelines and Framework Law (Lei de Diretrizes e Bases da Educacao LDB) of 1996, to be developed as curricula by education systems across the country. In Sao Paulo, was defined a minimum and common curriculum for all schools, that was more seen into basic education from first to fourth grade by structuring the Reading and Writing Program in 2007. In this article we contextualize this program in a municipal school, contemplating reflections on teaching, the training curriculum and external evaluations. The methodology used was the qualitative and descriptive research by material analysis of the Reading and Writing Program and interviews with literacy teachers at the school.
Keywords: Curriculum; Didactic and teaching materials; External evaluations; Teacher's role